Mobile Diagnostic Assessment for Deepening Conceptual Mastery of LCM and GCD in Elementary Mathematics - Deti Rostika; Prihantini; Komariah; Muh. Asriadi AM (Journal of Education Reseach and Evaluation, 2025)
This study addresses the lack of valid, practical, and easily accessible diagnostic assessment tools for identifying elementary school students’ learning difficulties, particularly in the topics of Least Common Multiple (LCM) and Greatest Common Divisor (GCD). The purpose of this study is to design and validate a mobile-based diagnostic assessment instrument suitable for fifth-grade students. This development research employed the 4D model. The study involved experts in mathematics education and digital media, a fifth-grade classroom teacher, and 30 elementary school students. Data were collected through expert validation sheets, diagnostic test items, and teacher and student response questionnaires. Quantitative descriptive analysis and qualitative interpretation were applied. Aiken’s V coefficient was used to measure content validity, while practicality was analyzed through the percentage scores of user responses. Students’ diagnostic results were further examined using item difficulty indices and error pattern analysis. The results indicate that the developed mobile diagnostic tool achieved very high validity (Aiken’s V > 0.80) and high practicality (>85%). However, the diagnostic findings reveal that students’ conceptual understanding remains low, particularly in distinguishing between multiples and factors. These results underscore the importance of enhancing item diversity and integrating adaptive feedback features. This study contributes to the development of digital diagnostic tools aligned with the Kurikulum Merdeka, supporting adaptive, data-driven, and technology-enhanced learning in elementary mathematics.